The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1051/0004-6361/201732219
|View full text |Cite
|
Sign up to set email alerts
|

Helical magnetic fields in molecular clouds?

Abstract: Context. Magnetic fields pervade in the interstellar medium (ISM) and are believed to be important in the process of star formation, yet probing magnetic fields in star formation regions is challenging. Aims. We propose a new method to use Faraday rotation measurements in small-scale star forming regions to find the direction and magnitude of the component of magnetic field along the line of sight. We test the proposed method in four relatively nearby regions of Orion A, Orion B, Perseus, and California. Metho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
104
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(115 citation statements)
references
References 90 publications
11
104
0
Order By: Relevance
“…We note that the B-field angle derived from polarization observations is the true 3D angle projected onto the POS. To understand the actual structure of the B-field and its relationship with surrounding ISM, we need to take into account their respective 3D structures (e.g., Tomisaka 2015;Planck Collaboration et al 2016b;Tahani et al 2018). Moreover, Planck and BLASTPol observations have limited spatial resolutions (>2 5) that are not sufficient to trace the B-field orientation within filaments.…”
Section: Introductionmentioning
confidence: 99%
“…We note that the B-field angle derived from polarization observations is the true 3D angle projected onto the POS. To understand the actual structure of the B-field and its relationship with surrounding ISM, we need to take into account their respective 3D structures (e.g., Tomisaka 2015;Planck Collaboration et al 2016b;Tahani et al 2018). Moreover, Planck and BLASTPol observations have limited spatial resolutions (>2 5) that are not sufficient to trace the B-field orientation within filaments.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the effect of magnetic helicity on dust polarization power spectra, our first intuition is conservative within the interpretation frame of the correlation between density filaments and the magnetic field in the ISM. The existence of helical magnetic fields wrapped around the main axis of molecular filaments has been observed (Bally et al 1987;Matthews & Wilson 2002;Poidevin et al 2011;Tahani et al 2018), and is suggested to regulate the dynamics of such clouds against gravitational fragmentation (Fiege & Pudritz 2000;Toci & Galli 2015).…”
Section: Introductionmentioning
confidence: 99%
“…filament. More robust measurements of the field strength are needed (note the recent progress by Pattle et al 2017;Tahani et al 2018).…”
Section: Filament and Core Dynamicsmentioning
confidence: 99%